Microbiota da rizosfera de plantas de tomate cultivadas em substratos à base de composto pós-cultivo de cogumelos Agaricus - Moraes, Tatiana Silveira Junqueira de (2016)
The production of tomato seedlings is an important stage during the cultivation of this vegetable, given that its quality is normally associated to the success of production. There are different commercial substrates available in the market for the production of vegetable seedlings. However, alternative substrates can be used for both reducing production costs and for the production of higher quality seedlings. The use of Spent Mushroom Substrate – SMS, is an excellent alternative to commercial substrates for this purpose, since it allows a noble destination for the residue of the mushroom production chain, as well as contributes for the production of better quality seedlings. Previous papers showed that the use of Agaricus subrufescens SMS for the production of tomato seedlings resulted in higher productivity. Many factors can be involved in this positive effect, among which are the microbiota present in the SMS. Thus, it is important to know the microbiota present in this material and its relation to the plant, in order for this association to be done in the best manner possible. This work was conducted with the objective of identifying the microbiota present in the rhizosphere of tomato seedlings cultivated in SMS of species Agaricus subrufescens and Agaricus bisporus, added or not with commercial substrate, in addition of identifying the microbiota present in the commercial substrate (Tropstrato) and comparing the treatments. We used the seeds of tomato seedlings, cultivar Santa Cruz Kada (Solanum lycopersicum), which, after germination, were transplanted to pots containing the formulation of pure spent mushroom substrate, or associated to commercial substrates. From each treatment, samples of the root system were obtained, from which we extracted DNA with the objective of conducting molecular analysis by DGGE, and sequencing to identify the dominant species. The sequencing of the amplicons was conducted at Macrogen USA (Rockville, Maryland, USA), and the sequences were compared based on data from the GenBank. Among the eukaryotes, we found species of Chaetomium globosum, Arthrobotrys amerospora, Geastrum floriforme, Chrysosporium chiropterorum, Pleurotus sp, Trichosporon sp. and Candida mesorugosa. Among the prokaryotes, we found species of alpha proteobacteria, Actinoplanes sp., Aeromicrobium sp. and Caulobacter sp.